Peasants in power : the political economy of development and genocide in rwanda - Verwimp, Philip (Springer Netherlands, 2013)
This book shows how Rwanda's development model and the organisation of genocide are two sides of the same coin. In the absence of mineral resources, the elite organised and managed the labour of peasant producers as efficient as possible. In order to stay in power and benefit from it, the presidential clan chose a development model that would not change the political status quo. When the latter was threatened, the elite invoked the preservation of group welfare of the Hutu, called for Hutu unity and solidarity and relied on the great mass (rubanda nyamwinshi) for the execution of the genocide. A strategy as simple as it is horrific. The genocide can be regarded as the ultimate act of self-preservation through annihilation under the veil of self-defense.             Why did tens of thousands of ordinary people massacred tens of thousands other ordinary people in Rwanda in 1994? What has agricultural policy and rural ideology to do with it?  What was the role of the Akazu, the presidential clan around president Habyarimana?  Did the civil war cause the genocide? And what insights can a political economy perspective offer ? Based on more than ten years of research, and engaging with competing and complementary arguments of authors such as Peter Uvin, Alison Des Forges, Scott Strauss, René Lemarchand, Filip Reyntjens, Mahmood Mamdani and André Guichaoua, the author blends economics, politics and agrarian studies to provide a new way of understanding  the nexus between development and genocide in Rwanda. Students and practitioners of development as well as everyone interested in the causes of violent conflict and genocide in Africa and around the world will find this book compelling to read.